Tactile Sensing for Soft Robotic Manipulators in 50 MPa Hydrostatic Pressure Environments - Shaoyu Liu; Daohui Zhang; Xin Fu; Liyan Mo; Qile Miao; Rong Huang; Xin Huang; Wei Guo; Yangyang Li; Qingyang Zheng; Ganguang Yang; Kun Bai; et al. (Advanced Intelligent Systems, 2023)
Deep‐sea exploration remains a challenging task as the extreme hydrostatic pressure environment, darkness, and suspended sediment launch severely hinder the capability of deep‐sea vehicles. As a complement to underwater camera, tactile perception becomes especially important in situations where machine vision is limited. However, tactile sensors utilized in deep sea, which should be able to detect pressure changes of only hundreds of pascals under high hydrostatic pressure, are still lacking. To tackle the challenge imposed by hydrostatic pressure, a simulated deep‐sea environment flexible sensor (SDEFS) is proposed, consisting of a force sensor array and a bending sensor based on hydrogels for tactile sensing in 50 MPa hydrostatic pressure environments. The force sensor is unaffected by the hydrostatic pressure and achieves high sensitivity of 82.62 N−1 under 100 MPa hydrostatic pressure. The SDEFS is utilized to classify objects based on the difference in hardness. It can accurately classify seven objects on the ground, and three objects in an underwater environment with hydrostatic pressure of 50 MPa, with total recognition accuracies of 98.3% and 96%, respectively. With high force measurement sensitivity and accurate recognition ability under water, the SDEFS is expected to provide very valuable haptic sensing and feedback in deep‐sea exploration.